2015
DOI: 10.1371/journal.pone.0133304
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Worker Preferences for Active Tuberculosis Case Finding Programs in South Africa: A Best-Worst Scaling Choice Experiment

Abstract: ObjectiveHealthcare workers (HCWs) in South Africa are at a high risk of developing active tuberculosis (TB) due to their occupational exposures. This study aimed to systematically quantify and compare the preferred attributes of an active TB case finding program for HCWs in South Africa.MethodsA Best–Worst Scaling choice experiment estimated HCW’s preferences using a random-effects conditional logit model. Latent class analysis (LCA) was used to explore heterogeneity in preferences.Results“No cost”, “the assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…[78]Australia20153110324111115 O’Hara et al. [79]South Africa201512515125101114 Ratcliffe et al. [80]Australia2015119045109101002 Tsao et al.…”
Section: Resultsmentioning
confidence: 99%
“…[78]Australia20153110324111115 O’Hara et al. [79]South Africa201512515125101114 Ratcliffe et al. [80]Australia2015119045109101002 Tsao et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, facilitators in health systems are patient nancial support, quick testing time, appropriate counseling and testing, patient tracking, health worker training, quick and e cient work ows, su cient sta ng, free and con dential TB services [40,41,44,46,47,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…As we were the ones most directly involved with all the components of the research -from the formation of the collaboration, to planning the research agenda and designing the projects, to collecting and analyzing the data and synthesizing results for decision-makers and scholarly venuesour own perceptions, synthesized through the process of writing this article, provided the main source of data. The description was aided by reference to the over 10 publications already published from our collaboration [20,[43][44][45][46][47][48][49][50][51][52].…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…This study included 2 focus groups, key informant interviews, and distribution of a questionnaire at two hospitals in Free State. Analysis of results found that to improve uptake of TB screening by health workers, programs should be free, guaranteed, confidential, with minimal waiting times, and available at the workplace [52].…”
Section: Contextualizing Why and How The Canadian-south African Partnmentioning
confidence: 99%